PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN MEMBER DEWA RUCI GYM DI KABUPATEN JEMBER - Tri Palupi Robustin (UNEJ e-Proceeding)
This study aimed to examine the effect of: (1) quality of service partially to the satisfaction of the member Dewa Ruci Gym, (2) quality of service simultaneously to the satisfaction of the member Dewa Ruci Gym. The study design is based on the goal is including explanatory research (explanatory research). The study population is the member Dewa Ruci Gym, and samples taken as many as 40 respondents overall. Data were analyzed using multiple regression analysis using SPSS version 17. Hypothesis testing is done partially and simultaneously. The results showed that: (1) partially variable tangible, reliability, responsiveness, assurance, and empathy significant effect on the satisfaction of members of Dewa Ruci Gym, (2) simultaneously variable tangible, reliability, responsiveness, assurance, and empathy significant effect on satisfaction Gym member Dewa Ruci. The coefficient of determination (R square) of 87.2% means that the variable quality of service is able to explain the influence on satisfaction variable changes and the remaining 12.8% is explained by other variables.